Degree of Computer Teachers’ awareness of Artificial Intelligence Ethics in Riyadh - Alfaraj, Khulud Sulaiman; Alshgrawe, Luluwah Saad; Albalawi, Amirah Mohammed; Alobaika, Reem Abdulmohsen (Journal of Educational and Psychological Sciences, 2025)
The study aimed to explore the extent of awareness among computer science teachers about Artificial Intelligence Ethics in Riyadh and to examine variations in their awareness level based on years of experience. The study sample consisted of 92 secondary school computer science teachers. To achieve the objectives, a descriptive methodology was employed, using a questionnaire comprising 15 statements distributed across four axes: transparency, fairness, security, and accountability. The results indicated that the participants had a high level of awareness of Artificial Intelligence ethics in the axes of transparency, security, and accountability, but a lower level in the axis of fairness. Additionally, no statistically significant differences were found in the mean scores attributed to years of experience. In light of these findings, the study recommends training teachers in the ethics of Artificial Intelligence , particularly in the area of fairness. It also suggests conducting similar studies to assess teachers’ awareness of AI ethics in other specializations and educational stages.